Biological removal of the xenobiotic trichloroethylene (TCE) through cometabolism in nitrifying systems - KOCAMEMİ, BİLGE (ELSEVIER SCI LTD, 2010)
In the present study, cometabolic TCE degradation was evaluated using NH(4)-N as the growth-substrate. At initial TCE concentrations up to 845 mu g/L, WE degradation followed first-order kinetics. The increase in ammonium utilization rate favored the degradation of TCE. This ensured that biological transformation of TCE in nitrifying systems is accomplished through a cometabolic pathway by the catalysis of non-specific ammonia oxygenase enzyme of nitrifiers. The transformation yield (T(y)) of TCE, the amount of TCE degraded per unit mass of NH(4)-N, strongly depended on the initial NH(4)-N and TCE concentrations. In order to allow a rough estimation of TCE removal and nitrification at different influent TCE and NH(4)-N concentrations, a linear relationship was developed between 1/T(y) and the initial NH(4)-N/TCE ratio. The estimated T(y) values lead to the conclusion that nitrifying systems are promising candidates for biological removal of TCE through cometabolism. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Activated sludge; Cometabolism; Nitrification; Trichloroethylene; Xenobiotics; NITROSOMONAS-EUROPAEA; CHLORINATED SOLVENTS; AEROBIC COMETABOLISM; DEGRADATION; AMMONIA; INACTIVATION; KINETICS; BIODEGRADATION; INHIBITION; RECOVERY